A CRITICAL REVIEW OF THE CONCEPT OF RISK IN ISLAMIC FINANCE: ENLIGHTEN EVIDENCE FROM THE HOLY QURAN, HADITH AND SHARI’AH MAXIMS - Jamshid ur Rehman; Asghar Kamal (International Journal of Contemporary Issues in Social Sciences, 2024)
This study provides a description of the concept of risk exist in financial transaction from the perspective of the Quran, Sunnah, and Islamic classical literature. It also ascertains whether risk is synonyms with the terms Gharar (uncertainty) and Maysir (Gambling). Finally, it sheds light on the permissibility of risk recognition, identification and sharing, and taking of precautionary steps for mitigation and management. These objectives are achieved through critical analysis of Islamic and conventional financial literature. This research employed an inductive qualitative methodology. The inferences are drowned from the Qur’anic verses, authentic hadiths, and Shari’ah maxims. It is observed that Islamic scholars define risk in a way that is very consistent with the view of conventional economists. Since, both schools of thought define risk in a negative sense and have a consensus that eventually risk leads to losses. The concept of risk is embedded in the various verses of the Quran, Hadiths, and Shari’ah maxims. These sources not only recognize the concept of risk but also provide general guidelines to identify, monitor, and mitigate risk confronted in daily life and economic activities. Shari’ah defines guidelines for risk-taking for instance, Shari’ah prohibits those activities in which gambling (Maysir) is involved and where gharar-e-qaseer arise. Moreover, the literature reveals that the concept of risk is not synonymous with the concept of gharar. While, gharar-e-qasser invalidates the contract, whereas risk falls under the domain of minor gharar, which is permissible.